Generation of local symmetry-preserving operations on polyhedra - Goetschalckx, Pieter (Ars mathematica contemporanea, 2020)
We introduce a new practical and more general definition of local symmetry-preserving operations on polyhedra. These can be applied to arbitrary embedded graphs and result in embedded graphs with the same or higher symmetry. With some additional properties we can restrict the connectivity, e.g. when we only want to consider polyhedra. Using some base structures and a list of 10 extensions, we can generate all possible local symmetrypreserving operations isomorph-free.
Keywords: chamber systems; graph theory; poliedri; polyhedra; simetrija; sistemi komor; symmetry; teorija grafov